WEB-BASED POPULATION DATA COLLECTION INFORMATION SYSTEM IN TEMA TANA VILLAGE - Marlince Saingo; Adelbertus Umbu Janga; Alexander Adis (JTH: Journal of Technology and Health, 2023)
The Village Information System is an inseparable part of the implementation of Village laws. Village Law Article 86 concerning Village Development Information Systems and Rural Area Development clearly states that villages have the right to access information through information systems developed by regional or city governments. A system is a group of elements that are closely related to each other, which function together to achieve certain goals. Hardware and software. Hardware includes one notebook unit with eighth generation Intel Core i3 specifications, 4 Gb RAM, 256 Gb SSD. The software used includes the Windows 10 Pro 64bit operating system, Notepad++, XAMPP, Chrome, Microsoft Word, Microsoft Visio. The results obtained from this research are an administrative information system that can solve the problems faced by Tema Tana Village. From the results of the discussion it can be concluded that the administrative information system can answer the problems faced, including easier and faster data searching, data archiving does not take up much space. large because it has been replaced by digital storage, and data reporting can be presented quickly, completely, attractively and according to office need